Design of Bolts or Rivets Subject to Combined Shear and Tension - Zweig, Alfred (Engineering Journal, 1966)
The 1963 AISC specification introduced, in Section 1.6.3, new provisions pertaining to the combined tension and shear stresses in bolts and rivets. The formulas given in this section permit the checking of a given design but leave the design itself to a rather cumbersome cut and try procedure. The purpose of this paper is to present a simple method which enables the designer or detailer to establish the required number of bolts or rivets in a bracket connection—the most common case in which rivets or bolts are under combined action of shear and tension (see Fig. 1). The specification provides different criteria for various rivet types, high tensile bolts of the friction or bearing type and for unfinished bolts; for this reason a different analysis is required for each ofthese elements. This paper will deal, however, only with the most commonly used types, that is, ASTM A325 type high tensile bolts and A141 rivets.